DOWNWARD COMMUNICATION & EQUIVOCALITY REDUCTION IN CORPORATE CORE VALUES ADAPTATION LEVEL - Harris Christanto; Rustono Farady Marta; Changsong Wang; Mary Rose Montano; Engliana (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2026)
Every institution upholds distinctive core values and expects its members to adapt accordingly. PT Kimia Farma (Persero) Tbk, the first pharmaceutical company in Indonesia, introduced a new set of core values, “AKHLAK,” on July 1, 2020. This study aims to provide a descriptive analysis of how downward communication typology and equivocality reduction contribute to employees’ adaptation to these new core values. The introduction of “AKHLAK” presents a valuable opportunity to evaluate the effectiveness of downward communication within the organization. The study employs an explanatory quantitative approach. The survey population consisted of 245 employees, with a sample of 152 participants selected through proportional stratified random sampling. The results indicate that downward communication typology contributes 37.2% to employees’ adaptation to the new core values, while equivocality reduction accounts for 59% of the contribution. When considered simultaneously, the two variables explain 61.9% of the adaptation level. Regarding the adaptation level itself, most employees fall into the early majority category, with an overall adaptation level considered moderate. In conclusion, both downward communication typology and equivocality reduction have significant contributions—both individually and jointly—toward employees’ adaptation to the organization’s new core values. The study recommends that all members of the company continue to strengthen their adaptation capabilities over time to fully align with the core values.